Análise estatística da precipitação pluviométrica em Belém-PA - CARDOSO, Felipe de Farias (2022)
This study analyzes the temporal variability of rainfall over 19 years. Rainfall is an important factor in the climatic characteristics of a city, linked to other meteorological events and the geographic situation. The application of statistical techniques to meteorological data has the advantage of compacting the enormous volume of measured data, capable of simplifying all information, facilitating data processing. This research statistically analyzes the rainfall in the city of Belém-PA to obtain the annual and monthly averages of the event during the period from 2003 to 2021, verifying the variation of rainfall in each year studied. Climatic data from the National Institute of Meteorology (INMET) were processed using MS Excel software. In the annual analysis, it was found that precipitation averaged 0.19 mm/h and the months with the highest and lowest rainfall were March and July.